A study of the awareness of college students of Arellano University, Far Eastern University, and University of the East on plagiarism and proper citation - Dujua, Alexis P. (2014)
This study aimed to find out the awareness of college students of Arellano University, Far Eastern University and University of the East on the concept of plagiarism and proper citation with the use of a survey questionnaire. The researcher developed a scoring device that was used to interpret the gathered responses from the respondents.